The phonotactics of English coda: A case study of Yemeni Speakers of English. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2007)
The arabic language phonology system plays an important role in the production of second language phonology of Arab speakers of English, particularly with regard to language transfer.